Honeybee keeping constraints and future prospects - Mulatu Wakgari; Gebissa Yigezu (Cogent Food & Agriculture, 2021)
Beekeeping is important for securing food, poverty reduction, health, environmental protection and plant pollination. These important practices are challenged by many biotic and abiotic factors in recent years. These factors affect honeybees and their valuable products either in combination or alone. The climatic factors like extreme temperature, relative humidity, shortage of water, deforestation of floral plants, human factors like poor apicultural practices, synthetic pesticides, diseases, and arthropod pests led to the decline of honeybee colonies and their products. But the world market demand for honey and other hive products has increased tremendously in recent decades since it is important for a wide variety of uses and applications. This review paper, therefore, was aimed at exploring these major constraints in beekeeping. It also outlines the most important cultural methods with emphasis on sanitation, maintaining bee colony vigor and some other management practices. Furthermore, from the conclusion of the review, it became important to recommend establishing specific laws and legislations that might be issued by decision makers to prevent honey adulteration. It also requires organizing honey marketing channels and raising awareness on limiting the use of pesticides in agriculture to protect the bees and the environment as well. The renovations and application of improved beekeeping technologies not only benefits beekeepers but also farmers and the general public in pollinating their crops, maintaining plant biodiversity, and the ecology at large. This review, therefore, addresses the honeybee and its production constraints and puts forward some available management practices.